Cloud based agricultural field parameters monitoring using ESP8266 and ZigBee - Samkaria, Rohit; Singh, Rajesh; Gehlot, Anita; Choudhary, Sushabhan (International Journal of Engineering and Technology, 2018)
To improve the production of agricultural, monitoring of the different parameters in the field has been proven to be the powerful tool. With the advent of technology crop monitoring may be achieved at very precise level; however Wireless Sensor Area Network result in low power and low cost deployments and Cloud based field monitoring is becoming a dominant option. So a method has been developed for agricultural systems that act as phonological indicators of various seasonal developments in the field and number of climate effect upon the regional growth over the crop for a broad region using (IoT) Internet of Things. The developed platform has been evaluated for various field parameters, creating a WSAN with a base station to record various parameters and finally uploaded this parameter to the Internet server. The performance result of the developed system has shown the feasibility and confirms its future aspects in broad sense.Â Â Â
Keywords: IOT; WSN; ZigBee; Cloud Computing